The Main Approashes for Increasing the Efficiency of the Rural School Network - Tyshkevych, Olga; Obidniy, Aleksandr (International Journal of Engineering and Technology, 2018)
The purpose of the article is to identify the main directions of improvement of the network of institutions of general secondary education in rural areas on the example of Ukraine. The authors developed an algorithm for research, consisting of four stages. During the study, the preconditions for forming a network of rural schools were considered. The following network parameters such as warehouse, spatial structure are found. Based on the analysis of modern socio-pedagogical requirements, the concept of promising organization of school services in rural areas has been developed. It is established that in conditions of rural settlements, it is advisable to form teams for teaching from pupils of different ages (multigrade classes). The authors provided suggestions on the formation of territorial educational districts as a promising direction for improving the network of rural schools. The perspective types of institutions of general secondary education, which are formed on the basis of interagency integration with other objects of cultural and household services of the population, are revealed. To improve the process of designing a network of village schools, the authors developed a methodology for optimizing the network of schools on the basis of linear programming.Â